PROPHET’S MEDICINE AMONG THE CONTEMPORARY INDONESIAN SALAFI GROUPS - Jajang Jahroni (IAIN Tulungagung, 2020)
The old-centuries medical forms claimed to have been exemplified by the Prophet Muhammad, called Prophet’s medicine, have been reinvented by the contemporary Indonesian Salafis. This invention is parts of their attempts to return all aspects of life to the authoritative resources. In doing so, the Salafis use modern packaging to attract non-Salafi Muslims. As a result, Prophet’s medicine has been popular among certain Muslim groups. The presence of Prophet’s medicine, to some extent, challenges conventional medicine which is hardly affordable by the average people. This is made possible by an open political climate which occurs in Indonesia over the last two decades. It eventually leads to the diversity of medicinal knowledge in the country.